Cuproptosis-related genes score: A predictor for hepatocellular carcinoma prognosis, immunotherapy efficacy, and metabolic reprogramming - Nie, Guilin; Peng, Dingzhong; Wen, Ningyuan; Wang, Yaoqun; Lu, Jiong; Li, Bei (Frontiers in Oncology, 2023)
Abstract Background: Cuproptosis is a newly identified type of programmed cell death, characterized by aggregation of mitochondrial lipoylated proteins and the destabilization of Fe–S cluster proteins triggered by copper. However, its role in hepatocellular carcinoma (HCC) remains unclear. Methods: We analyzed the expression and prognostic significance of cuproptosis-related genes using the data obtained from TCGA and ICGC datasets. A cuproptosis-related genes (CRG) score was constructed and validated via least absolute shrinkage and selection operator (LASSO) Cox regression, multivariate Cox regression and nomogram model. The metabolic features, immune profile and therapy guidance of CRG-classified HCC patients were processed via R packages. The role of kidney-type glutaminase (GLS) in cuproptosis and sorafenib treatment has been confirmed via GLS knockdown. Results: The CRG score and its nomogram model performed well in predicting prognosis of HCC patients based on the TCGA cohort (training set), ICGC cohort and GEO cohort (validation set). The risk score was proved as an independent predictor for overall survival (OS) of HCC. The area under the curves (AUCs) of the model in the training and validation cohorts were all around 0.83 (TCGA, 1- year), 0.73 (TCGA, 3- year), 0.92 (ICGC, 1- year), 0.75 (ICGC, 3- year), 0.77 (GEO, 1- year), 0.76(GEO, 3- year). Expression levels of metabolic genes and subtypes of immune cells, and sorafenib sensitivite varied significantly between the high-CRG group and low-CRG group. One of the model-included gene, GLS, might be involved in the process of cuproptosis and sorafenib treatment in HCC cell line. Conclusion: The five cuproptosis-related genes model contributed to prognostic prediction and provided a new sight for cuproptosis-related therapy in HCC. Keywords: Cuproptosis; hepatocellular carcinoma; prognostic model; sorafenib; GLS